PENGARUH BUDAYA ORGANISASI DAN PELATIHAN KERJA DENGAN SISTEM PENDIDIKAN TERHADAP PRODUKTIVITAS KINERJA KARYAWAN PADA PT. PLN (PERSERO) UNIT INDUK PEMBANGUNAN SUMATERA UTARA - Muhammad Agung Anggoro; Sondang Merci Yulisandy Halawa; Dosmasri Sibuea; Cindy Christin Br. Tarigan; David Evelyn Suranta Sinulingga (Universitas Methodist Indonesia, 2020)
The research aims to examine the effect of organizational culture, job training, and education system on employee performance. The research method used by researchers is a quantitative approach, the type of research is quantitative descriptive. The population used was all employees by 68 people and the number of samples used were all employees by 68 people. The data collection method was done by interviews, questionnaires and also study documentation. The analytical method used was multiple linear regression. The results show that organizational culture, job training and the education system simultaneously and partially have a significant effect on increasing employee performance productivity with a coefficient of determination of 0.307 which indicates that organizational culture, work training and education systems influence employee productivity performance with a level of percentage 30.7% while the remaining 69.3% are other factors not examined such as motivation, age, gender, rewards and punishments.